Lysophosphatidic acid counteracts glucagon-induced hepatocyte glucose production via STAT3 - Evan P. Taddeo (Nature Portfolio, 2017)
Abstract Hepatic glucose production (HGP) is required to maintain normoglycemia during fasting. Glucagon is the primary hormone responsible for increasing HGP; however, there are many additional hormone and metabolic factors that influence glucagon sensitivity. In this study we report that the bioactive lipid lysophosphatidic acid (LPA) regulates hepatocyte glucose production by antagonizing glucagon-induced expression of the gluconeogenic enzyme phosphoenolpyruvate carboxykinase (PEPCK). Treatment of primary hepatocytes with exogenous LPA blunted glucagon-induced PEPCK expression and glucose production. Similarly, knockout mice lacking the LPA-degrading enzyme phospholipid phosphate phosphatase type 1 (PLPP1) had a 2-fold increase in endogenous LPA levels, reduced PEPCK levels during fasting, and decreased hepatic gluconeogenesis in response to a pyruvate challenge. Mechanistically, LPA antagonized glucagon-mediated inhibition of STAT3, a transcriptional repressor of PEPCK. Importantly, LPA did not blunt glucagon-stimulated glucose production or PEPCK expression in hepatocytes lacking STAT3. These data identify a novel role for PLPP1 activity and hepatocyte LPA levels in glucagon sensitivity via a mechanism involving STAT3.